Studi Korelasi Hipertensi Gestasional dengan Kejadian BBLR di Wilayah Kerja Puskesmas Arjuno Kota Malang - Fitriyah, Nuroatul; Nurrochmah, Siti; Alma, Lucky Radita (Preventia: The Indonesian Journal of Public Health, 2021)
ndonesia ranks ninth in the world for the highest number of LBW cases, with a percentage exceeding 15.5% of births in 2018. The trend of LBW incidence in East Java increased from 2016 (3.6%) to 2017 (3.8%). In 2018, Arjuno Health Center experienced an upward trend in the prevalence of Low Birth Weight (LBW) cases, rising from 4.5% to 9.0%, and ranked first with the highest LBW prevalence in Malang City. Hypertension in pregnancy is common and is a leading cause of maternal mortality during childbirth, as well as having other serious effects during delivery. This study aims to determine the correlation between gestational hypertension and the incidence of LBW in the working area of Arjuno Health Center in 2019. The research design used a case-control design, with purposive sampling as the sampling method. The case group consisted of 31 subjects, and the control group consisted of 62 subjects, resulting in a total sample of 93 individuals. Data collection was conducted through documentation using maternal cohorts, MCH handbooks, and village midwife recapitulation records of LBW cases in 2019. The bivariate analysis used was the contingency coefficient test. The results of the contingency coefficient test showed a significant relationship between gestational hypertension and the incidence of LBW (p-value = 0.000, r = 0.4, OR = 12.4, 95% CI = 0.198–0.524).